The impact of antibiotic induction on virulence and antibiotic resistance in Klebsiella pneumoniae: a comparative study of CSKP and CRKP strains - Chen, Ke-Da; Chen, Wei; Zhang, Qian; Li, Qingcao (Frontiers in Microbiology, 2024)
Background: Klebsiella pneumoniae is an opportunistic pathogen causing nosocomial infections, classified into carbapenem-sensitive and carbapenem-resistant strains. Understanding the virulence factors and antibiotic resistance of these strains is essential for effective clinical management.Objective: This study compared the virulence genes and antibiotic resistance profiles of 50 CSKP and 50 CRKP strains, examining their expression under antibiotic pressure and the mechanisms contributing to their pathogenicity.Methods: Virulence genes (rmpA, rmpA2, iucA, iutA, ybts, iroB) were detected in both strains using polymerase chain reaction (PCR). Antibiotic susceptibility testing established minimum inhibitory concentrations (MICs) for key antibiotics. Gene expression analysis was performed with quantitative reverse transcription PCR (qRT-PCR) after 10 days of antibiotic exposure.Results: CSKP strains exhibited significantly higher positivity rates for virulence genes compared to CRKP strains. CRKP strains predominantly expressed resistance genes KPC, SHV, and CTX-M3, whereas no resistance genes were found in CSKP. Antibiotic susceptibility tests showed increased MICs, particularly for ciprofloxacin and imipenem, following antibiotic induction. CSKP demonstrated elevated expression of rmpA and rmpA2, while CRKP showed increased expression of iutA, SHV, and KPC after antibiotic exposure.This study highlights the intricate relationship between virulence and resistance in Klebsiella pneumoniae. CSKP strains show strong virulence factor expression, while CRKP strains adapt to antibiotic pressure through altered gene expression patterns. These findings underscore the urgent need for continuous surveillance and innovative therapeutic strategies to combat multidrug-resistant Klebsiella pneumoniae infections.